An integrated buyer initiated decision-making process for green supplier selection. (October 2016) - Jain, Vipul; Kumar, Sameer; Kumar, Amit; Chandra, Charu
Highlights: Proposes an environmentally friendly industrially validated approach for supplier selection. Inclusive of a comprehensive carbon market model for suppliers. Approach based on Data Envelopment Analysis. Provides framework for environmental regulations to be modeled. Incorporates heterogeneous suppliers and encourages suppliers to "Go Green". Abstract: Organizations have been under growing pressure to reduce emissions across their supply chains while cutting supply costs to remain competitive. This paper proposes a Carbon Market Sensitive (CMS) and a green decision making approach based on Data Envelopment Analysis (DEA) called CMS–GDEA. It builds on an existing Green DEA model and modifies it to include a carbon market model. Results from the model validation in a well known automobile spare parts manufacturer in India indicate that the "Pay Up" factor from carbon trading adds a new dimension to competition among suppliers and increases overall supply chain profitability. The proposed approach encourages suppliers to go green and cut down their carbon footprints or "Pay Up" to comply with the emission norms along with cutting costs, which adds to healthy competition.